Improving Medication Adherence in Diabetics through Education and Training in Self-Monitoring of Blood Glucose in Samarinda: Kepatuhan Minum Obat pada Penderita Diabetes melalui Edukasi dan Pemantauan Glukosa Mandiri di Samarinda - Alwan Darwissy Annaza; Yasmine Nur Fachriyyah; Rayhan Fajar Rahmat; Islamudin Ahmad (B-Creta Publisher, 2026)
Type 2 diabetes mellitus (T2DM) represents a major public health problem due to its increasing prevalence and the complexity of its long-term management. Effective control of T2DM relies heavily on patient adherence to pharmacological therapy, including oral antidiabetic drugs and insulin, as well as routine self-monitoring of blood glucose levels. However, in many communities, inadequate knowledge, misconceptions about treatment, and limited practical skills remain significant barriers to optimal disease management. In Samarinda City, the high number of diabetes cases reflects ongoing challenges in improving therapy compliance and empowering patients to actively participate in self-care practices. Community-based interventions play an important role in addressing these challenges by providing accessible education and hands-on training tailored to local needs. Health education that combines theoretical information with practical demonstrations has been shown to improve understanding, foster positive attitudes, and enhance self-efficacy among people with diabetes. Furthermore, the use of pre-test and post-test evaluations allows for an objective assessment of knowledge improvement following educational interventions. By strengthening community knowledge and skills related to medication adherence and blood glucose monitoring, such programs have the potential to contribute to better glycemic control, reduce the risk of complications, and support sustainable diabetes management at the community level.